Synthesis and characterization of mixed ligand complexes of caffeine, adenine and thiocyanate with some transition metal ions - Shayma A. Shaker,; Yang Farina,; Sadia Mahmmod,; Mohean Eskender, (Universiti Kebangsaan Malaysia, 2010)
An ethanolic solution of caffeine was added to an aqueous solution of metal salts and followed by adding ethanolic solution of adenine and an aqueous solution of potassium thiocyanate to give complexes with general formula [M(CA)2(Ad)X2] where CA is caffeine, Ad is adenine, X is thiocyanate ion and M is Co(II), Ni(II), Cu(II), Zn(II) and Cd(II). The resulting products were characterized using UV-visible and infrared spectroscopies. Elemental analyses were performed using C, H, N analysis and atomic absorption techniques. The magnetic susceptibility and the conductivity were also measured. The results suggested that the complexes have octahedral geometry.